2021
DOI: 10.1111/cas.15116
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA AC020978 facilitates non–small cell lung cancer progression by interacting with malate dehydrogenase 2 and activating the AKT pathway

Abstract: Lung cancer is the most common cancer, accounting for approximately 1.6 million deaths or 28% of all deaths from cancer globally each year. 1 Clinical research has shown that 81% of patients with clinically detected lung cancer live for less than 5 years. In addition, most cases are diagnosed at a distant stage because of the typically asymptomatic nature of the early stages of the disease. 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Both the PI3K/AKT and ERK signaling pathways are classical signaling pathways involved in tumorigenesis, 51,52 and numerous studies have confirmed that AKT/ERK promotes NSCLC progression. 53,54 On one hand, our team had proved that ERK pathway can be activated by ACAT1 in prostate cancer to regulate tumor cells proliferation, migration, and invasion.…”
Section: Dars-as1 Knockdown Inhibits Tumor Growth In Nude Micementioning
confidence: 99%
“…Both the PI3K/AKT and ERK signaling pathways are classical signaling pathways involved in tumorigenesis, 51,52 and numerous studies have confirmed that AKT/ERK promotes NSCLC progression. 53,54 On one hand, our team had proved that ERK pathway can be activated by ACAT1 in prostate cancer to regulate tumor cells proliferation, migration, and invasion.…”
Section: Dars-as1 Knockdown Inhibits Tumor Growth In Nude Micementioning
confidence: 99%
“…Increasing evidence has indicated that Long non-coding RNAs (lncRNAs) [ 5 ] regulate cancer metastasis-related signaling pathways via interacting with microRNA, mRNA and proteins, such as HOTAIR [ 6 ], AC020978 [ 7 ] and TMEM220-AS1 [ 8 ]. This highlights the dual nature of lncRNAs with both tumor suppressor and oncogene functions in cancers.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has indicated that long non-coding RNAs (lncRNAs) [5] regulate cancer metastasisrelated signaling pathways via interacting with microRNA, mRNA and proteins, such as HOTAIR [6], AC020978 [7] and TMEM220-AS1 [8]. This highlights the dual nature of lncRNAs with both tumor suppressor and oncogene functions in cancers.…”
Section: Introductionmentioning
confidence: 99%